2001
DOI: 10.1063/1.1343881
|View full text |Cite
|
Sign up to set email alerts
|

On combined standard–nonstandard or hybrid (q,h)-deformations

Abstract: Combined (q, h)-deformations proposed by Kupershmidt and Ballesteros-Herranz-Parashar are studied. In each case a transformation is shown to lead to an equivalent, standard q-deformation. We briefly indicate that appropriate singular limits of the same type of transformations can however lead from standard biparametric (p, q)-deformations to non-hybrid but biparametric nonstandard (g, h) ones. Finally a case of hybrid (q, h)-deformation is recalled, related to the superalgebra GL(1|1).

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…The procedure is generalizable to any other Lie algebra with one or other deformation, but also to quantum algebras with hybrid deformations, i.e, quantum algebras combining both kinds of deformations [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…The procedure is generalizable to any other Lie algebra with one or other deformation, but also to quantum algebras with hybrid deformations, i.e, quantum algebras combining both kinds of deformations [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Studying the classification of [8] we noticed altogether five nonsingular such R-matrices. The triangular ones were introduced in [7] and their duals were found and studied in detail in [9]. In the latter paper we called these bialgebras exotic.…”
Section: Introductionmentioning
confidence: 99%
“…For the supergroup GL(1|1) there are also two: the standard GL pq (1|1) [3][4][5] and the hybrid (standard-nonstandard) GL qh (1|1) [6] two-parameter deformations. Recently, in [7] it was shown that there are no more deformations of GL (2) or GL(1|1). In particular, it was shown that these four deformations match the distinct triangular 4 × 4 R-matrices from the classification of [8] which are deformations of the trivial R-matrix (corresponding to undeformed GL(2)).…”
Section: Introductionmentioning
confidence: 99%
“…In the classification of [8] there are altogether five nonsingular such R-matrices. The three triangular ones were introduced in [7] and their duals were found and studied in detail in [9]. The study of the two non-triangular cases was started in [10].…”
Section: Introductionmentioning
confidence: 99%
“…The list, of course, includes the four cases which are deformations of classical ones: two two-parameter deformations of each of GL (2) and GL(1|1), namely, the standard GL pq (2) [1], nonstandard (Jordanian) GL gh (2) [2], the standard GL pq (1|1) [3][4][5] and the hybrid (standardnonstandard) GL qh (1|1) [6]. (Later, in [7] it was shown that there are no more deformations of GL (2) or GL(1|1).) The list includes also five exotic cases which are not deformations of the classical algebra of functions over the group GL(2) or the supergroup GL(1|1).…”
Section: Introductionmentioning
confidence: 99%